Chromosome 17 Aneusomy Detected by Fluorescence in Situ Hybridization in Vulvar Squamous Cell Carcinomas and Synchronous Vulvar Skin - Carlson, J. Andrew (American Society for Investigative Pathology, 2000)
Vulvar squamous cell carcinoma (SCC) affects a spectrum of women with granulomatous vulvar diseases, human papillomavirus (HPV) infections, and chronic inflammatory vulvar dermatoses. To determine whether there is evidence of chromosomal instability occurring in synchronous skin surrounding vulvar SCCs, we investigated abnormalities in chromosome 17 copy number. Samples of SCC, vulvar intraepithelial neoplasia (VIN), and surrounding vulvar skin were obtained from all vulvar excisions performed for squamous neoplasia at Albany Medical College from 1996 to 1997. Histological categorization, fluorescent in situ hybridization (FISH) for the α satellite region of chromosome 17, DNA content by image analysis, and Ki-67 labeling were evaluated. Controls of normal vulvar skin not associated with cancer were used for comparison. One hundred ten specimens were obtained from 33 patients with either SCC or VIN 3 and consisted of 49 neoplastic, 52 nonneoplastic, and 9 histologically normal vulvar skin samples. The majority of SCCs (88%) and a minority (18%) of VIN 3 excisions were associated with lichen sclerosus. Normal vulvar skin controls did not exhibit chromosome 17 polysomy (cells with more than four FISH signals), whereas 56% of normal vulvar skin associated with cancer did. Moreover, the frequency of polysomy significantly increased as the histological classification progressed from normal to inflammatory to neoplastic lesions. The largest mean value and variance for chromosome 17 copy number was identified in SCCs (2.4 ± 1.0) with intermediate values identified, in decreasing order, for SCC in situ (2.1 ± 1.0), VIN 2 (2.1 ± 0.8), lichen sclerosus (2.0 ± 0.5), lichen simplex chronicus (1.9 ± 0.4), and normal skin associated with SCC (1.8 ± 0.4) compared with control vulvar skin (1.5 ± 0.05). Concordance of chromosome 17 aneusomy between cancers and synchronous skin lesions was found in 48% of patients. Loss of chromosome 17 was identified 5% of all samples and was significantly associated with women with SCC in situ (HPV-related). Both DNA content and Ki-67 labeling positively and significantly correlated with mean chromosome 17 copy number (r = 0.1, P = 0.007). A high degree of genetic instability (aneuploidy) occurs in the skin surrounding vulvar carcinomas. As these events could be detected in histologically normal skin and inflammatory lesions (lichen sclerosus), chromosomal abnormalities may be a driving force in the early stages of carcinogenesis. Differences in chromosomal patterns (loss or gain) support the concept of at least two pathways in vulvar carcinogenesis.